DEFENCE PROCUREMENT IN SUPPORTING THE PRODUCTION OF WEAPONS AND MILITARY EQUIPMENT - Hmyria, Viktoriia; Kobets, Yuriy (Collection of scientific papers «ΛΌГOΣ», 2025)
Under martial law, defence procurement plays a key role in ensuring the combat capability of the Armed Forces of Ukraine and other security forces. They cover a wide range of goods, services and works, from basic needs (food, administrative support) to high-tech weapons and military equipment.